An Exploration of Identity and Generational Conflict in Graham Swift’s Last Orders - Alam, Md Imteyaz; Jha, Nilima (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Graham Swift’s Last Orders explores the search for identity and conflict between generations. The novel focuses on tense relationships between fathers and sons. It shows how the values and choices of older generations shape the lives of the younger ones. During a final journey together, the characters look back on their past. They face hidden emotions and responsibilities passed down to them. Last Orders shows that identity is shaped by memory, relationships, and generational conflict, not by personal freedom alone.